Effects of dietary energy level and intake of corn by-product based diets on newly received growing cattle - Spore, Tyler J. (Kansas State University, 2017)
Four pen studies and one digestibility trial were conducted to evaluate the effects of energy level and intake of corn by-product based diets on newly received growing cattle. In Exp.1 there were four diets where one was offered for ad libitum intake and formulated to supply 0.99 Mcal NEg/kg DM (0.99/100) and the other three treatments were fed at 95, 90, and 85% of the ad libitum treatment and to supply 1.10 (1.10/95), 1.21 (1.21/90), and 1.32 Mcal NEg/kg DM (1.32/85), respectively. ADG was unaffected by treatment (P = 0.32). However, G:F increased linearly with increasing energy and decreasing intake level (P < 0.01). In Exp. 2, a digestibility trial was conducted to study diets from Exp. 1. Ruminal propionate linearly increased with increasing dietary energy and decreasing intake (P < 0.01). Total tract DM digestibility increased linearly with increasing energy and decreasing intake (P < 0.01), whereas passage rate decreased (P < 0.01). Experiment 3 validated results from Exp. 1 feeding the 1.10/95 treatment at 2.40% of BW daily and the 1.32/85 treatment at 2.2% of BW daily and studied a DNA-immunostimulant (Zelnate, Bayer Animal Health, Shawnee Mission, KS). Zelnate had no effect on parameters measured. ADG was not different between energy treatments (P = 0.75), but efficiency was greater for the 1.32/85 treatment (P = 0.03). Experiment 4 was designed to observe effects of the 1.32 Mcal NEg/kg DM diet fed at four intake levels of 1.9, 2.2, 2.5, and 2.8 % of BW daily. ADG increased linearly with increasing intake (P < 0.01), however G:F was not affected (P = 0.98). In Exp. 5 a factorial design was employed to evaluate the effects of two by-products; wet corn gluten feed and wet distiller’s grains plus solubles, and two levels of corn processing; whole corn or dry-rolled corn. Final ADG and G:F were not affected by by-product, corn processing, or their interaction (P > 0.30). Additionally, animals and diets from Exp. 1 were used to study effects on antibody production, acute phase protein response, stress, and immunocompetency of healthy and morbid cattle. Diet had no effect on the parameters measured (P > 0.10). A quadratic response to time (P < 0.01) was detected for haptoglobin, titers for bovine viral diarrhea type 1 (BVD-1), and infectious bovine rhinotracheitis (IBR). Haptoglobin was highest on d 14, and close to baseline levels by d 27. Titer levels for BVD-1 and IBR were higher on d 14, and significantly higher on d 27. Titers for bovine viral diarrhea type 2 (BVD- II) responded linearly (P < 0.05) to time with the highest levels on d 27. Haptoglobin was elevated in morbid animals compared to healthy pen mates (P < 0.05). Titer levels for BVD-I and IBR were higher in healthy animals (P < 0.01). Fecal cortisol was higher on arrival than on d 14 (P < 0.05). In summary, high-energy limit-fed diets based on corn by-products do not affect health and are more efficient than when roughage-based growing diets are fed.
Keywords: Limit-feeding; Programmed-feeding; By-products; ImmunityStocker cattle